Community Nursing Care with Knowledge Deficit Problems About Low Salt Diet in Hypertension Respondents in Punaga Hamlet, Bajeng District, Gowa Regency - Muhamad Isnaini (Sean Institute, 2022)
This research aims to reveal and know the description of nursing care regarding adherence to a low salt diet in hypertension respondents. This research was conducted in Punaga Hamlet, Maradekaya Village, Bajeng District, Gowa Regency with respondents who experienced hypertension which took place from June to July 2022. The observation was used as a data collection technique. Then the data analysis techniques used in achieving research using qualitative descriptive analysis include data reduction, data presentation, and conclusion. The results of the study revealed that after education about hypertension and a low-salt diet, the respondents understood the education that had been delivered and there was an effect of education, namely increasing knowledge about a low-salt diet in hypertension respondents. There is an influence of hypertension education and a low-salt diet on hypertension respondents and their families so that the client's family understands their illness, if foods high in salt can trigger hypertension, and families can find out the right way of handling hypertension.